Has Goodwill Become More Relevant After IFRS Convergence in Indonesia? - Ersa Tri Wahyuni; Dewantoro Dewantoro; Ilya Avianti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
This research aims to analyze the value relevance of goodwill in Indonesia before and after International Financial Report Standard (IFRS) convergence. Prior to the IFRS convergence period, goodwill should be amortized, while after the IFRS convergence the amortization was prohibited and goodwill should be tested for impairment on annual basis. This research investigates goodwill among Indonesian listed companies in Kompas 100 index for the period 2009-2015. Using panel data regression analysis, the research finds before the IFRS adoption, both goodwill and goodwill amortization did not have significant value to the market value of the companies. However, goodwill has significant value to the market price of after IFRS convergence (2011-2015), while goodwill impairment losses did not. We also found more companies recording impairment loss at the adoption year than the years afterward. We tested the significance of impairment loss around the year of adoption and the test shows goodwill impairment loss has significant value to the market price of the companies. Thus, the adoption of IFRS 3 which required goodwill impairment has improved the value relevance of goodwill. The adoption of IFRS 3 also encouraged the companies to impair their goodwill at the adoption year. Impairment loss had been perceived positive by the investors which are shows by its positive sign of goodwill impairment coefficient. This may indicate Indonesian investors appreciate the purification of goodwill number from hidden past impairment and anticipate the higher future of Return on Asset.